Ordinances of the Town of North Kingstown an Ordinance Establishing the Ordinances of the Town of North Kingstown, and Prescribing the Time When They Shall Go into Effect, at 6, ch. 6, § 1. - (:unkn) unknown (General Publisher, 1896)
Every person who shall play at ball, or any other game or sport, throw stones or other missiles, discharge any gun, pistol, or other fire-arms, fire any torpedo, fire-cracker, or other noisy missile in any public place, street, or highway in this town, shall, on conviction thereof, pay a fine of not less than one dollar, nor more than five dollars, for every such offense.
--
Keywords: DISCHARGE